2021
DOI: 10.1186/s12935-021-02228-9
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive TDO2 expression promotes liver cancer progression by an autocrine IL-6 signaling pathway

Abstract: Background Increased tryptophan (Trp) metabolism by indoleamine 2,3-dioxygenase (IDO)/tryptophan 2,3-dioxygenase (TDO) represents one of the most studied pathways for immunosuppression in tumor tissues. However, the pro-tumor effects induced by Trp metabolism remain controversial. Methods The paraffin sections of tumor tissues were obtained from patients with liver cancer and examined by immunohistochemical staining to investigate the role of Trp m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In the present study, we identified that TDO2 is highly expressed in 20 types of cancer, including BLCA, BRCA, CESC, COAD, ESCA, GBM, HNSC, KIRC, LUAD, LUSC, OV, PAAD, PRAD, READ, SKCM, STAD, TGCT, THCA, UCEC, and UCS, which are in line with previous findings [8][9][10][24][25][26][27][28]. However, Wu et al found that TDO2 was overexpressed in HCC, and their overexpression was correlated with tumor progression and poor prognosis [29,30], which contradicts our current results. On the other hand, Yu et al investigated the expression of TDO2 in HCC tissues compared with paired adjacent normal tissues and found that there was downregulation of TDO2 expression in HCC, which agrees with our results [31].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we identified that TDO2 is highly expressed in 20 types of cancer, including BLCA, BRCA, CESC, COAD, ESCA, GBM, HNSC, KIRC, LUAD, LUSC, OV, PAAD, PRAD, READ, SKCM, STAD, TGCT, THCA, UCEC, and UCS, which are in line with previous findings [8][9][10][24][25][26][27][28]. However, Wu et al found that TDO2 was overexpressed in HCC, and their overexpression was correlated with tumor progression and poor prognosis [29,30], which contradicts our current results. On the other hand, Yu et al investigated the expression of TDO2 in HCC tissues compared with paired adjacent normal tissues and found that there was downregulation of TDO2 expression in HCC, which agrees with our results [31].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to SLAMF7, no studies have reported a role for TDO2 in DM or ILD. However, in other diseases, such as hepatocellular carcinoma, it has been found that TDO2 expression contributes to the secretion of interleukin-6 (IL-6), which promotes tumour cell proliferation through STAT3 and NF-kB/TIM4 signalling [29]. In osteoarthritis patients, TDO2 levels were signi cantly and positively correlated with IL-1β and TNF-α levels, suggesting that high levels of TDO2 in the synovium may correlate with pro-in ammatory cytokines and the severity of osteoarthritis [30].…”
Section: Discussionmentioning
confidence: 99%
“…The recent determination of the metabolic landscape of cancer cell lines confirms that accumulation and secretion of kynurenine are correlated with IDO (mainly IDO1 ) and TDO transcriptional expression, with some cancer cell lines expressing both enzymes [ 61 ]. In vivo, the serum kynurenine/tryptophan ratio has been directly associated with either IDO1 or TDO2 expression and is correlated with disease progression in multiple cancer types, including breast, lung, colon and liver carcinomas [ 62 , 63 , 64 , 65 ]. Notably, while IDO1 is overexpressed in gliomas, the kynurenine/tryptophan ratio is not predictive of disease progression in that tumor model [ 66 ], suggesting that the biological significance of this ratio is not universal.…”
Section: Consequences Of the Activation Of The First Immunosuppressiv...mentioning
confidence: 99%
“…Mechanistically, both IDO1-driven tryptophan depletion and AhR activation contribute to cytokine production [ 70 , 71 ]. In liver cancer, the production of IL6 in response to the activation of TDO2-kynurenine-AHR signaling was also demonstrated to activate STAT3 and NF-κB/TIM4 signals to sustain cell proliferation, demonstrating additional protumoral properties of autocrine IL6 signaling pathways [ 65 ].…”
Section: Consequences Of the Activation Of The First Immunosuppressiv...mentioning
confidence: 99%